LiOH/Coconut Shell Activated Carbon Ratio Effect on the Electrical Conductivity of Lithium Ion Battery Anode Active Material - Annisa Syifaurrahma; Arnelli Arnelli; Yayuk Astuti (Molekul, 2021)
A lithium ion battery anode active material comprised of LiOH (Li) and coconut shell activated carbon (AC) has been synthesized with Li/AC ratios of (w/w) 1/1, 2/1, 3/1, and 4/1 through the sol gel method. The present study aims to ascertain the best Li/AC ratio that produces an anode active material with the best electrical conductivity value and determine the characteristics of the anode active material in terms of functional groups, surface area, crystallinity, and capacity. Based on the electrical conductivity test using LCR, the active material Li/AC 2/1 had the highest electrical conductivity with a value of 2.064x10-3 Sm-1. The conductivity achieved was slightly smaller than that of the active material with no addition of LiOH on the activated carbon at an electrical conductivity of 5.434x10-3 Sm-1. The FTIR spectra of the activated carbon and Li/AC 2/1 showed differences with in the Li-O-C group absorption at 1075 cm-1 wavenumber and the wide absorption in the area of 547.5 cm-1 that represents Li-O vibration. Based on the results of SAA, the activated carbon had a larger surface area than Li/AC 2/1 at 17.057 m2g-1 and 5.615 m2g-1, respectively. The crystallinity of both active materials was low shown by the widening of the diffraction peaks. Tests with cyclic voltammetry (CV) proved that there was a reduction-oxidation reaction for the two samples in the first cycle with a large charge and discharge capacities of the activated carbon of 150.989 mAh and 92.040 mAh, while for Li/AC 2/1 they were 91.103 mAh and 47.580 mAh.